Procedure And Methods of Control. - Teshaboeva N.D. (Zien Journals, 2022)
In the state of readiness and inferiority, the procedure is provincial. Measures will be developed to analyze the condition of the facility and eliminate identified defects. Assessment of the condition of the object as a result of direct inspection provides preliminary information about the structure under inspection, analysis of the degree of decay in the structural elements, the need for further inspection.
Keywords: Impacted; defective elements; objects; dynamic details